Rancang Bangun Prototype Solar Panel Cleaning Otomatis Berbasis Arduino Uno - Ramadan, Bayu; Muzakkir, Taufik; Fadillah, Nurul (Jurnal ELIT, 2024)
West Kalimantan Province has abundant renewable energy potential, especially solar energy generated through solar cells. Solar panels are the primary tools for converting sunlight into electricity, used for both household and public infrastructure purposes. This study designs an automatic cleaning system to overcome the challenges of manual cleaning, such as panel damage, work-related accidents, and spatial and distance limitations. The system uses wipers and water spraying, controlled by an Arduino Uno microcontroller equipped with an RTC DS3231 module. Test results show that the system can clean solar panels efficiently without the risk of damage or accidents. The voltage produced increased from 20.05V on dusty panels to 20.38V after cleaning with water and wipers, and reached 21.08V when the panels were clean and dry. This system has been proven to enhance the efficiency of solar panels.